Kinematics Analysis on 3-DOF Orthogonal Translational Parallel Mechanism Platform - Ge Zhenghao; Bai Pengyu; Han Xiaohu; Liu Xuesong (Jixie chuandong)
In order to study the platform of orthogonal three-degree-of-freedom translational parallel mechanism， the platform configuration of the parallel mechanism is designed， and the corrected Kutzabach-Grubler freedom formula is used to verify that the output of the parallel mechanism platform is a three-degree-of-freedom motion. According to the geometric relationship between different components， the various movements of the branched chain constraint equations between angle and swing arm are explored. The position positive solution equation and inverse solution equation are established according to the geometric constraint relationship between the motion coordinates and fixed coordinates. The speed and acceleration expressions of the parallel mechanism platform are obtained. Finally， the kinematics simulation is carried out according to the set motion law parameters， and the reference point is set on the motion platform. And the motion trajectory of the motion platform and the related motion law curve are obtained， and the dynamic performance of the parallel mechanism platform is verified.